Counseling and Guidance Understandings of Guidance Teachers and Their Attitudes Towards Counseling and Guidance - Demir Güdül, Meryem; Can, Gürhan (My University, 2015)
In this study, it was aimed to study the relationships between counseling and guidance understanding of guidance teachers, who are in charge of giving counseling and guidance service to a class, and their attitudes towards counseling and guidance, and how their understanding of counseling and guidance and their attitudes towards counseling and guidance differentiate in terms of various variables. Within the framework of relational screening model, the Counseling and Guidance Inventory (Kepçeoğlu, 1975) and the Guidance Counselor Attitude Scale (Demir, 2010) were used in the study, which was conducted with 595 guidance teachers working in primary and secondary education institutions in Eskişehir. As a result of the study, it was determined that there was a moderate level relationship (r= .44) between guidance teachers’ understanding level of counseling and guidance and their attitude levels towards counseling and guidance. The female guidance teachers were found to have higher understanding of counseling and guidance and attitudes towards counseling and guidance than those of the male teachers. It was also determined that the guidance teachers’ understanding of counseling and guidance and their attitudes towards counseling and guidance did not differentiate in terms of branch. On the other hand, the guidance teachers who attended the in-service training about counseling and guidance were found to have more positive attitudes only towards counseling and guidance than the ones who didn’t attend the in-service training, whereas the guidance teachers working in primary education were found to have higher levels of both counseling and guidance understanding and attitudes towards counseling and guidance than the ones working in secondary education in terms of the stage of education the teachers work in. Similarly, the counselors who had 1-9 and 10-19 years of seniority had higher counseling and guidance understandings than the ones who had 20 and more years of seniority. The findings obtained as a result of the study were discussed in the light of relevant literature.
Keywords: Understanding of counseling and guidance; Attitude towards counseling and guidance; Guidance counselor; Counseling and guidance services in schools